How Do Gender, Sexuality, and Age Impact Perceptions of Teacher Sexual Misconduct? An Intersectional Vignette-Based Study. (January 2022) - Russell, Kristan N.; Gruys, Kjerstin
In this study we investigate the intersecting impacts of perpetrators' gender, sexuality, and age on perceptions of teacher sexual misconduct. When the teacher was a woman, respondents perceived the relationship to be less detrimental to the student, the student to be more mature and responsible, and the relationship as more acceptable. Heterosexual pairings were perceived as more acceptable than same-sex pairings, with the student perceived as more mature and responsible. Lastly, when the teacher was older respondents perceived them as more responsible and the student as having psychological issues contributing to the relationship.